Antiproliferative activity from various fraction chloroform extract of muntingia calabura / Muhammad Fikri Musa - Musa, Muhammad Fikri (2009)
The aim of the present study is to determine the in vitro antiproliferative activity of chloroform extract of Muntingia calabura leaves (CEMC) and its fractions against human acute myelocytic leukemia (HL-60), human lung adenocarcinoma epithelial (A549) and human breast adrenocarcinoma (MCF-7) cell lines using 3-(4,5-dimethylthiazol-2-il)-2, 5-diphenil tetrazolium bromide (MTT) kit assay. The diluted ranges of extract were added to each well and the final concentrations of the test extracts were 1.56, 3.13, 6.25, 12.50, 25.00, and 50.00 µg/ml. CEMC possessed antiproliferative activity only against HL-60 with an IC50 of 41.25 µg/ml with no effect seen against normal fibroblast (3T3) cell line. Fractionation of CEMC yielded eleven (11) fractions whereby only 3 fractions, namely F2, F4 and F5 fractions showed antiproliferative activity on the cancer cell but do not inhibit the proliferation of 3T3 cells, thus, indicating its safety. F2 was effective against MCF-7 (IC50 of 9.75 µg/ml), HL-60 (IC50 of 12.50 µg/ml) and A549 (IC50 of 31.20 µg/ml); F4 was effective against HL60 (IC50 of 11.25 µg/ml), A549 (IC50 of 37.07 µg/ml) and MCF7 (ICso of 46.00 µg/ml) and; F5 exerted antiproliferative activity against HL-60 (IC50 of 11.25 µg/ml) and A549 (ICso of 49.50 µg/ml). In conclusion, CEMC possess potential anticancer activity that needs to be further explored.